Studi Perbandingan Library Untuk Implementasi Network Automation Menggunakan Paramiko Dan Netmiko Pada Router Mikrotik - Luis Geraldo Mauboy; Theophilus Wellem (STMIK Budi Darma, 2022)
In recent years, network automation has emerged as a solution to the impracticality of manually configuring network devices by network administrators. By implementing network automation, network administrators can configure and manage network devices automatically using scripts or software that is run from one of the hosts or servers in the network. This paper aims to conduct a comparative study through the implementation of cases for network automation. Four scenarios are taken as examples for the implementation of network automation, among others, static routing, dynamic routing, network address translation (NAT), and simple network management protocol (SNMP). The automation scripts are realized using Python libraries, namely Paramiko and Netmiko. Tests and simulations were carried out using the GNS3 simulator software with a network topology consisting of two Mikrotik routers, one Ethernet switch, one Network Automation server, and two computers as clients. The experiment results show that automation using the Paramiko library is better than automation using the Netmiko library in terms of the time required for the execution of configuration scripts. The average execution time for the four implemented scenarios is 3.66 seconds.